Steppe islands in a sea of fields: Where island biogeography meets the reality of a severely transformed landscape. (13th September 2020) - Dembicz, Iwona; Moysiyenko, Ivan I; Kozub, Łukasz; Dengler, Jürgen; Zakharova, Maryna; Sudnik‐Wójcikowska, Barbara
Abstract: Questions: Steppes are among the most transformed and fragmented biomes in the world, but studies on the impact of habitat loss and fragmentation on these zonal grasslands are scarce. In many regions, steppe has survived only on small habitat islands, particularly on kurgans (ancient burial mounds) surrounded by intensive croplands. We asked how the size of kurgans, their isolation and other landscape and local factors influence their species richness. Location: Southern Ukraine. Methods: We recorded all species of vascular plants and assessed local (area, steepness, disturbance level), landscape (distance to the nearest habitat patch, habitat amount in the surroundings, surrounding type, distance to settlements) and climatic (precipitation) conditions of 112 kurgans. We analysed species–area relationships (SARs) for total richness, habitat specialists and generalists. Then, we assessed importance of environmental factors in explaining the residuals of the SAR models. Results: Patch area explained more than 50% of variance in total and specialist species richness. The slopes of the power function SAR ( z ‐values) were higher for specialists than for generalists. Connectivity measures (the distance to the nearest large habitat enclave and share of habitat in the surroundings) were more important for richness of specialists than for that of generalists, which were more controlled by the kurgan's surroundings. Conclusions: We found that for specialist species the steppe "islands" follow the theory of island biogeography closely, but less so for generalist species. Combined with the revealed importance of connectivity for specialist species richness, we conclude that the conservation value of the kurgans in the long term likely can only be achieved with larger steppe areas in the surroundings. Abstract : Kurgans (ancient burial mounds) constitute small steppe habitat islands within the "sea of fields" forming the landscape of southern Ukraine. We found that they can function nearly as "oceanic islands, " particularly for steppe vascular plant species as their richness is strongly controlled and positively related with kurgan size, landscape‐scale connectivity and local‐scale habitat heterogeneity indices.